2015
DOI: 10.1108/el-10-2013-0193
|View full text |Cite
|
Sign up to set email alerts
|

The effects of online service quality of e-commerce Websites on user satisfaction

Abstract: Purpose – The purpose of this paper is to investigate service quality of e-commerce Websites in online platform and their contribution on e-business promotion. Design/methodology/approach – The online survey was performed on a survey portal provided by Nepal Telecom in Nepal. Findings – The findings of this study suggest that information quality and online service quality were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 55 publications
6
104
0
17
Order By: Relevance
“…This result has been confirmed within previous literature. For instance, Sharma and Lijuan's (2015) study posited the positive association between information quality and e-commerce website usability. Algharabat and Shatnawi (2014) posited that information quality reflected by ease of use has a direct impact on website usability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result has been confirmed within previous literature. For instance, Sharma and Lijuan's (2015) study posited the positive association between information quality and e-commerce website usability. Algharabat and Shatnawi (2014) posited that information quality reflected by ease of use has a direct impact on website usability.…”
Section: Discussionmentioning
confidence: 99%
“…The author indicated that specific product information positively related to consumer's attitude towards the website (positively or negatively). Sharma and Lijuan (2015) showed that information quality, e-service quality and usefulness are directly linked to e-commerce website usability. The authors assert that information quality and online service quality are the key determinants for user satisfaction and sustainability of e-commerce technology.…”
Section: Information Quality and Usabilitymentioning
confidence: 99%
“…Originally, the growth of this very segment of electronic commerce market was really intensive and played a part of the driving force for electronic commerce development in other industries in foreign countries and in Russia as well. The available historical data give the possibility to size up the prospects and expected growth rates of the consumer goods market and also to lay the groundwork for the growth in other industries (Cambra-Fierro, Iguácel & Javier, 2017;Gajendra & Wang, 2016;Alderete, 2017).…”
Section: Analysis Of the Foreign And Domestic Experience Of Electronimentioning
confidence: 99%
“…The website is one of the measurement tools in ecommerce activities with page rank as the first indicator that reflects the quality of the website [2]. If the website has a poor ranking, analysis and evaluation are needed to improve visitor ratings by fixing the existing weaknesses of the site [3].…”
Section: Introductionmentioning
confidence: 99%
“…This research resulted in 11 dimensions, which became the standard for evaluating service quality on the site. This dimension was then developed to improve the quality of online shopping measurements, such as the dimensions of website design, reliability, responsiveness, trust, and personalization [10], aspects of information quality, e-service quality, usefulness, e-satisfaction, and trust [2].…”
Section: Introductionmentioning
confidence: 99%